2019
DOI: 10.1029/2019jg005028
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Carbonate Saturation State and Air‐Sea CO2 Fluxes During an Annual Cycle in a Stratified‐Temperate Fjord (Reloncaví Fjord, Chilean Patagonia)

Abstract: Changes may be occurring in the carbonate chemistry of fjords due to natural and anthropogenic disturbance of major freshwater sources. We present a high‐frequency time series study of seasonal pH and CO2 partial pressure (pCO2) in a north Patagonian fjord with a focus on changes in freshwater inflows and biological processes. To do this, we monitored pH and pCO2 in situ, along with river streamflow, salinity, temperature, and dissolved oxygen (DO) in the Reloncaví Fjord (41.5°S) for a full year (January to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 99 publications
(160 reference statements)
1
12
1
Order By: Relevance
“…Due to the pronounced seasonality of marine high latitude ecosystems, the productive period is limited to spring and summer (from October to mid-March, Almandoz et al, 2011) when the net uptake of CO 2 exceeds the community respiration, creating a net sink of CO 2 (Torres et al, 2011). During the remaining months, Chl-a concentration falls to < 1 µg Chl-a L −1 (Almandoz et al, 2011) and heterotrophic processes tend to dominate (e.g., Torres et al, 2011;Vergara-Jara et al, 2019). In a scenario of intensive aquaculture, we might expect higher loads of dissolved and particulate organic matter as well as an increase in nutrients (N and P mainly), which will primarily be remineralized by heterotrophic organisms, thus increasing pCO 2 levels and altering the carbonate chemistry of the seawater.…”
Section: Chemical Features Along the Beagle Channelmentioning
confidence: 99%
“…Due to the pronounced seasonality of marine high latitude ecosystems, the productive period is limited to spring and summer (from October to mid-March, Almandoz et al, 2011) when the net uptake of CO 2 exceeds the community respiration, creating a net sink of CO 2 (Torres et al, 2011). During the remaining months, Chl-a concentration falls to < 1 µg Chl-a L −1 (Almandoz et al, 2011) and heterotrophic processes tend to dominate (e.g., Torres et al, 2011;Vergara-Jara et al, 2019). In a scenario of intensive aquaculture, we might expect higher loads of dissolved and particulate organic matter as well as an increase in nutrients (N and P mainly), which will primarily be remineralized by heterotrophic organisms, thus increasing pCO 2 levels and altering the carbonate chemistry of the seawater.…”
Section: Chemical Features Along the Beagle Channelmentioning
confidence: 99%
“…Based on our data, the undersaturation levels of O cal and O arg were registered during autumn-winter season and relatively saturated conditions were registered during spring-summer season. Similarly, Vergara-Jara et al [43] shown strong seasonal variability of pH and pCO 2 in the Reloncaví fjord, Chilean Patagonia, with the undersaturation levels of O arg in winter and saturated conditions of aragonite in the summer. Our study shows the first time series of temperature and salinity associated with the parameters of the carbonate system within the Chilean oyster farm.…”
Section: Discussionmentioning
confidence: 78%
“…Our study shows the first time series of temperature and salinity associated with the parameters of the carbonate system within the Chilean oyster farm. The environmental conditions described for the Quempillén estuary share similarities with other estuaries in the region, such as a marked seasonal cycle characterized by minimum values of temperature and pH during the winter [43]. However, the intensity and timing of freshwater input to the estuary, as well as its concomitant effects on salinity and speciation of carbon chemistry, are expected to vary in association with local hydrographic characteristics (eg.…”
Section: Discussionmentioning
confidence: 96%
“…The system's stratification varies along the fjord and between seasons, decreasing toward the mouth and being maximum in winter. The Reloncaví Fjord has been extensively studied by several research projects, mainly oceanographic, including paleoclimate (Rebolledo et al, 2015), fjord hydrodynamics (Valle-Levinson et al, 2014;Castillo et al, 2016), fjord biogeochemistry (Farías et al, 2017;González et al, 2019;Vergara-Jara et al, 2019;Yevenes et al, 2019) and plankton biology (González et al, 2013;Iriarte et al, 2017).…”
Section: Study Areamentioning
confidence: 99%